2018
DOI: 10.4236/ojmm.2018.84008
|View full text |Cite
|
Sign up to set email alerts
|

Burden of Hepatitis B Viral Infection among Workers in a Tertiary Health Institution in Southwestern Nigeria

Abstract: Background: Health care workers (HCWs) are particularly at risk of hepatitis B virus (HBV) infections due to contact with infectious material like contaminated blood and body fluids or contact with HBV contaminated fomites. HBV vaccine is efficient in preventing infection though 5%-10% of individuals are non-responders. HBV vaccine was introduced into Nigerian childhood immunization services in year 2004. However, routine vaccination of HCWs is often not implemented due to cost in resource limited settings lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
(19 reference statements)
0
0
0
Order By: Relevance
“…The mean age of the respondents in this study was 32.41±0.32 years with the majority of the workers aged above 40 years. This is similar to research done in Edo state, southern Nigeria and Ado-Ekiti, southwest Nigeria to assess factors influencing knowledge of HBV vaccination among healthcare workers with a mean age of 34.90±9.46 years (2) and 35.00±4.50 years (18), respectively. The majority of the respondents were females (66.8%) with a similar occurrence in another study (18) with 66.5% females.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The mean age of the respondents in this study was 32.41±0.32 years with the majority of the workers aged above 40 years. This is similar to research done in Edo state, southern Nigeria and Ado-Ekiti, southwest Nigeria to assess factors influencing knowledge of HBV vaccination among healthcare workers with a mean age of 34.90±9.46 years (2) and 35.00±4.50 years (18), respectively. The majority of the respondents were females (66.8%) with a similar occurrence in another study (18) with 66.5% females.…”
Section: Discussionsupporting
confidence: 65%
“…This is similar to research done in Edo state, southern Nigeria and Ado-Ekiti, southwest Nigeria to assess factors influencing knowledge of HBV vaccination among healthcare workers with a mean age of 34.90±9.46 years (2) and 35.00±4.50 years (18), respectively. The majority of the respondents were females (66.8%) with a similar occurrence in another study (18) with 66.5% females. The majority (64.7%) of the respondents in this study demonstrated good knowledge of HBV infection.…”
Section: Discussionsupporting
confidence: 65%